2015
DOI: 10.1002/art.39127
|View full text |Cite
|
Sign up to set email alerts
|

Familial Risk of Sjögren's Syndrome and Co‐aggregation of Autoimmune Diseases in Affected Families: A Nationwide Population Study

Abstract: ObjectiveTo investigate familial aggregation of Sjögren's syndrome (SS) and the relative risks (RRs) of other autoimmune disease in relatives of patients with SS.MethodsWe identified 23,658,577 beneficiaries enrolled in the Taiwan National Health Insurance system in 2010, of whom 12,754 had SS. We identified 21,009,551 parent–child relationships and 17,168,340 pairs of full siblings. The familial risks of SS and other autoimmune diseases, tetrachoric correlation, and familial transmission were estimated.Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 41 publications
2
57
1
5
Order By: Relevance
“…Genetic and environmental factors probably contribute to phenotypic variance in SjS and a recent study has attributed 54% of the predisposition to developing the disease to familial transmission (heritability plus shared environmental factors) and 46% to non-shared environmental factors 27. Geoepidemiology and ethnicity should be considered as key variables that should be analysed in multi-ethnic studies of patients with primary SjS.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic and environmental factors probably contribute to phenotypic variance in SjS and a recent study has attributed 54% of the predisposition to developing the disease to familial transmission (heritability plus shared environmental factors) and 46% to non-shared environmental factors 27. Geoepidemiology and ethnicity should be considered as key variables that should be analysed in multi-ethnic studies of patients with primary SjS.…”
Section: Discussionmentioning
confidence: 99%
“…In a population-based family study of 105 Taiwan patients with SS who had an affected first-degree relative, Kuo et al [86] found a relative risk (RR) for SS in siblings of patients with SS to be 18.99, 11.31 in offspring, and 12.46 in parents. In first-degree relatives of SS patients the RR were 6.25 for having systemic lupus erythematosus, 3.38 for multiple sclerosis and 2.95 for rheumatoid arthritis [86]. …”
Section: Pathogenesismentioning
confidence: 99%
“…The etiology of pSS is not well understood 8 , and probably includes environmental triggers in genetically predisposed subjects, as illustrated by its familial aggregation 9 and predisposing genetic variants 10 . It mainly affects middle-aged females, with a strong sex bias potentially explained by an X chromosome dose effect 11 .…”
Section: Introductionmentioning
confidence: 99%